Changing Values: Attitudes about Intimate Partner Violence in Immigrants and Natives in Five Western Countries. Issue 3 (4th March 2017) - Rodriguez Martinez, Pilar; Khalil, Huzefa
ABSTRACT: This article explores attitudes about Intimate Partner Violence Against Women (IPVAW) amongt immigrant (first and second generation) and native populations in five post-industrial societies (Germany, Netherlands, New Zealand, Sweden, and USA). Using the sixth wave of World Values Survey, we conclude that there are significant differences, after controlling for demographic factors, between all three sub-populations in attitudes about IPVAW, with first generation immigrants more supportive of IPVAW than either natives or second generation immigrants. We also show that, for the three sub-populations, interactions of attitudes regarding interpersonal violence, gender equality and sexual tolerance are good predictors of attitudes about IPVAW.